Acquired venous aneurysms. Issue 3 (September 1991) - Paes, T; Andrews, S; Wyatt, A
Abstract : A case is reported of acquired venous aneurysms in the superficial forearm veins of an oarsman. The aetiology, presentation and complications are discussed.